Food allergen introduction practices and parent/caregiver attitudes based on family history of food allergy - Smith, Hunter G.; Nimmagadda, Sai; Gupta, Ruchi S.; Warren, Christopher M. (Frontiers in Allergy, 2025)
BackgroundThe National Institute of Allergy and Infectious Disease (NIAID) addendum guidelines for primary prevention of peanut allergy1 provide recommendations regarding peanut introduction, and a recent consensus statement highlighted the importance of timely introduction of other commonly allergenic solids, and the role of family history as a risk factor.2ObjectiveTo determine whether children in households with a food allergic parent/caregiver or sibling have different rates of being fed commonly allergenic solids during the first year of life than children lacking this family history.MethodsA pretested survey was administered between January-February 2021 to a U.S. sample of 3,062 parents/caregivers of children born since the NIAID Addendum guidelines. Survey-weighted chi-square statistics and logistic regression models tested the independence of key variables across strata of interest before and after covariate adjustment.ResultsPeanut, almond, shellfish, and other tree nuts are more likely to be introduced to children with one or more food-allergic caregivers. Respondents with food-allergic parents (39.3%) and siblings with FA (35.8%) were more familiar with the 2017 NIAID guidelines compared to parents (12.9%) and siblings without FA (12.7%).ConclusionFindings suggest that respondents with food-allergic parents and siblings are more likely to have many of the most prevalent allergens introduced at younger ages, which could be due to knowledge related to the NIAID-sponsored guidelines and other national guidance, but that even among these higher-risk families overall rates of “early” introduction during infancy still remain relatively low.